Pengaruh Partisipasi Penyusunan Anggaran Terhadap Kinerja Aparat Pemerintah Dengan Komitmen Organisasi, Budaya Organisasi, dan Desentralisasi Sebagai Variabel Moderasi - EKA BUDI SETYANINGTYAS (Universitas Muhammadiyah Semarang, 2019)
This study aims to examine the effect of budgetary participation on the performance of local government officials with organizational commitment, organizational culture, and decentralization as moderating variables at the Central Java Province Industry and Trade Office. The sample in this study were structural employees of the Dinperindag who were involved in the budget preparation process. The sampling method in this research is purposive sampling. The number of samples used was 47 respondents from 291 structural officials in the Dinperindag of Central Java province. The data validity test used Pearson Product Moment correlation test, while the reliability test used Cronbach Alpha. The data analysis technique used is simple and multiple regression analysis. The results of this study indicate that budgetary participation has a positive effect on the performance of local government officials as evidenced by the t value greater than the t table (3.574> 1.690) and a significance value (0.001 <0.05). Organizational commitment has a positive effect on the relationship between budgeting participation and the performance of local government officials, while organizational culture and decentralization have no effect on the relationship between budgetary participation and the performance of local government officials